2019
DOI: 10.47102/annals-acadmedsg.v48n12p412
|View full text |Cite
|
Sign up to set email alerts
|

Sun Exposure and Sun Safety Habits Among Adults in Singapore: A Cross-Sectional Study

Abstract: Introduction: Sun exposure increases skin cancer risk. Studies have shown that demographic factors influence sun safety behaviour but there is a paucity of such data in Singapore. We aimed to identify sociodemographic predictors of sun safety habits in Singapore. Materials and Methods: A total of 2328 adults participated in a cross-sectional survey on time spent under the sun and sun safety habits (using protective headgear, body attire, umbrellas and sunscreens). A composite Sun Protection Score (higher score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…These groups are more likely to use products that contain photoallergens, such as sunscreens, and seek medical attention for dermatological complaints. Locally, men and younger adults engage in sun protection habits less regularly, which may explain their lower representation in our study 6 …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These groups are more likely to use products that contain photoallergens, such as sunscreens, and seek medical attention for dermatological complaints. Locally, men and younger adults engage in sun protection habits less regularly, which may explain their lower representation in our study 6 …”
Section: Discussionmentioning
confidence: 69%
“…Locally, men and younger adults engage in sun protection habits less regularly, which may explain their lower representation in our study. 6 The reduced frequencies of PACD and photocontact allergy in Note: Percentages in each row do not add up to 100% as some patients are represented in more than one column.…”
Section: Discussionmentioning
confidence: 99%
“…Among 2,989 participants, Clermont et al discovered that individuals with lower educational levels (87.1%) tended to add more salt to meals consumed at home [ 31 ]. In another study, lower educational attainment was found to be a statistically significant predictor of longer sunlight exposure(β = -0.18, p < 0.001) [ 32 ]. In a questionnaire survey conducted by researchers, participants were interviewed regarding environmental, dietary, and genetic risk factors.…”
Section: Discussionmentioning
confidence: 99%